Cultural Approach in Responding to the Crisis of Public Trust: Sleman Government's Strategy in Encouraging COVID-19 Vaccination - Apriliani, Riski; Abisono, Firya Qurratu’ain (UI Scholars Hub, 2023)
In the case of the COVID-19 pandemic, it is necessary to reduce the risk of spreading COVID-19 through the vaccination program. Along with vaccination socialization, there is a lot of hoax information and disinformation related to vaccines which unfold distrust and reluctance among people to be vaccinated. However, it is different in the Special Region of Yogyakarta, especially the Sleman area, which has the highest vaccination rate and is declared to be completing the COVID-19 Vaccination in 11 months. This condition is an example of trust from the Sleman community listening to vaccination recommendations. The application of a cultural approach in increasing public trust to vaccinate against COVID-19 is also interesting to study further. Therefore, this study examines how the efforts to build public trust utilizing a cultural approach to crisis communication by the Department of Public Relations of the Sleman Government, which builds an image and manages the COVID-19 crisis, as well as being the Spokesperson for the COVID-19 Task Force. The research method used is a case study that explicitly discusses vaccination programs between January and May 2021. Data collection was done through in-depth interviews with the Department of Public Relations of the Sleman Government and secondary data through literature studies, related documents, and internet sources. The data analysis technique applies the approach of Miles and Huberman (1998), with data validation techniques through source triangulation. The efforts of the Department of Public Relations of the Sleman Government generated a high level of trust due to the decentralization policy which strengthened their relation with the community. The analysis results prove that the application of crisis communication by the Department of Public Relations of the Sleman Government intersects and supports each other on public trust in both the selection of actors, the preparation of messages, and the use of media. The coverage of elements of public trust present in the crisis communication of the COVID-19 Vaccination program proves that there is a link between effective crisis communication which has implications for high public trust.